2021
DOI: 10.3390/ijerph18041469
|View full text |Cite
|
Sign up to set email alerts
|

Communication Experiences in Primary Healthcare with Refugees and Asylum Seekers: A Literature Review and Narrative Synthesis

Abstract: Refugee and asylum seeker population numbers are rising in Western countries. Understanding the communication experiences, within healthcare encounters, for this population is important for providing better care and health outcomes. This review summarizes the literature on health consultation communication experiences of refugees and asylum seekers living in Western countries. Seven electronic databases were searched from inception to 31 March 2019. Studies were included if they aimed to improve, assess or rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…The results of the study revealed that the translation service shifted from being on site to a phone service during the pandemic. There were complaints about the quality of translation and a risk that health information was lost in communication where translators' lack of physical presence meant that they were not able to follow the non-verbal communication in the rooms at the health service centers, which could be confirmed by recent research that shows that following non-verbal communication could be a challenge for refugees during encounters within healthcare settings ( 46 ). Furthermore, there were different ways that refugees chose to protect their own health, but that social distancing was challenging due to crowded living and being isolated, which was challenging because there was a lack of physical space in crowded apartments.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study revealed that the translation service shifted from being on site to a phone service during the pandemic. There were complaints about the quality of translation and a risk that health information was lost in communication where translators' lack of physical presence meant that they were not able to follow the non-verbal communication in the rooms at the health service centers, which could be confirmed by recent research that shows that following non-verbal communication could be a challenge for refugees during encounters within healthcare settings ( 46 ). Furthermore, there were different ways that refugees chose to protect their own health, but that social distancing was challenging due to crowded living and being isolated, which was challenging because there was a lack of physical space in crowded apartments.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate communication can negatively impact on patient trust of healthcare services, it can also result in delayed and more costly health care (Migrant & Refugee Women's Health Partnership, 2019). While it is widely acknowledged that interpreter utilization in healthcare settings can be challenging for a variety of reasons, including inadequate funding, workforce shortages and time constraintshe finds this humiliating and a (Patel et al, 2021), it is best clinical practice to use interpreter services (Guzys et al, 2021). The use of appropriate language services and the right of a patient to access healthcare are inextricably linked.…”
Section: Nursing and Midwifery Contextmentioning
confidence: 99%
“…How this is experienced is shaped in part by patients' cultural views, language proficiency and patient's perceptions of the quality of care 11 . To support the accurate and accessible translation of key messages within the clinical consultation professional interpreters have been recommended to improve patient health outcomes 12,13 . However, even interpreters when taken up concerns have been reported about availability, access, confidentiality, and the accuracy of translation 5,14 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, even interpreters when taken up concerns have been reported about availability, access, confidentiality, and the accuracy of translation. 5,14 Some of these concerns with professional interpreter use could be negated through language concordant care between the healthcare provider and patient. Language concordant care is defined as situations where both the patient and healthcare provider speak to each other in their shared language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation